Analysis of Outpatient Satisfaction Levels with Pharmaceutical Services Using the Customer Satisfaction Index (CSI) Method - Negara, Sri Bintang Sahara Mahaputra Kusuma; Andriani, Medi; Muchtar, Melayusma (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
One of the objectives of pharmaceutical standards is to improve the quality of pharmaceutical services in community health centers and provide satisfactory services to patients. The objective of this study was to determine the level of patient satisfaction with pharmaceutical services at the pharmacy department of the Paal Lima community health center in Jambi City using the CSI method. This was a quantitative study with a descriptive, prospective design, involving the administration of questionnaires to patients who collected medication from the pharmacy department of the Paal Lima community health center. The results of the study showed patient satisfaction based on respondent characteristics: the majority were female (75 respondents, 75%), the majority were aged 26–35 years (37 respondents, 37%), the majority had a high school education (55 respondents, 55%), and the majority were housewives (58 respondents, 58%). Based on reliability dimension 75.6%, based on responsiveness dimension 72.8%, based on assurance dimension 73.8%, based on empathy dimension 82.6%, based on tangibility dimension 69.8%, with an average CSI score of 74.92%. The analysis reveals that patient satisfaction levels with pharmaceutical services at the Paal Lima Public Health Center Pharmacy in Jambi City, using the CSI (Customer Satisfaction Index) method, yielded a score of 74.92%, indicating that overall, patients are satisfied with the services provided.